Pervaporation-assisted crystallization of active pharmaceutical ingredients (APIs) - Claire Schmitz; Mohammed Noorul Hussain; Tom Meers; Zongli Xie; Liping Zhu; Tom Van Gerven; Xing Yang (Advanced Membranes, 2023)
Crystallization of active pharmaceutical ingredients is essential in pharmaceutical production. Pervaporation, a thermally-driven membrane process, has not been explored in API crystallization. Here we demonstrated PV-assisted crystallization (PVaC) for simultaneous recovery of API ortho-aminobenzoic acid (o-ABA) and pure solvent. The PERVAP 4060 made of organophilic polymer was found suitable given the reasonable flux of ethanol of 3.69 ​kg/m2/h at 45 ​°C with saturated solution and 99.9% o-ABA rejection. A parametric study showed that the membrane permeance increased with feed flow rate and temperature, but decreased with supersaturation. In the sequential PVaC, the stable form I of o-ABA was obtained with 25 ​°C PV; while with 45 ​°C PV, only metastable form II crystallized. In the simultaneous PVaC, at 0 time lag pure form II was produced; by increasing time lag, form I increased significantly. The results indicated potential routes to control polymorph formation via PVaC, providing a promising alternative for API production.